Online commercial refrigeration sale and service management system [electronic resource] - Wong, Fung Ring, 1988-, author (2012)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2012